2017
DOI: 10.17140/pcsoj-3-136
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression among Pregnant Women in the Gaza Strip

Abstract: Aim: This study aimed to examine the levels of anxiety and depression among pregnant women attending primary healthcare clinics in Gaza Strip. Method: The sample consisted of 400 pregnant women attending primary healthcare clinics in the Gaza Strip. They were interviewed using the sociodemographic scale, Hamilton Anxiety Rating Scale (HAM-A), and Beck Depression Inventory (BDI). Results: The study showed that 33.3% of the pregnant women showed moderate and 18.5% showed severe depression. Women living in refuge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Instead, there were some studies investigating the prevalence of anxiety disorders in general during pregnancy. For example, the prevalence of pregnancy-related anxiety in Saudi Arabia using state-anxiety scale was 23.6% [ 21 ], in Qatar it was 26.5% [ 22 ], 11.4 % in Egypt [ 23 ], and in the Gaza Strip 4.3% of pregnant women had moderate anxiety, and 8.8% had a severe form of anxiety [ 24 ]. In Jordan, in a cross-sectional study that was conducted to study the prevalence of anxiety among pregnant women attending routine obstetric care clinics, the researchers found that among 200 participants, 32 (16.0%) women had minimal symptoms, 60 (30.0%) had mild symptoms, 66 (33.0%) had moderate symptoms, and 42 (21.0%) had severe symptoms of anxiety [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, there were some studies investigating the prevalence of anxiety disorders in general during pregnancy. For example, the prevalence of pregnancy-related anxiety in Saudi Arabia using state-anxiety scale was 23.6% [ 21 ], in Qatar it was 26.5% [ 22 ], 11.4 % in Egypt [ 23 ], and in the Gaza Strip 4.3% of pregnant women had moderate anxiety, and 8.8% had a severe form of anxiety [ 24 ]. In Jordan, in a cross-sectional study that was conducted to study the prevalence of anxiety among pregnant women attending routine obstetric care clinics, the researchers found that among 200 participants, 32 (16.0%) women had minimal symptoms, 60 (30.0%) had mild symptoms, 66 (33.0%) had moderate symptoms, and 42 (21.0%) had severe symptoms of anxiety [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy has been defined as a period of well-being that has allowed women to feel biologically complete supported their emotional well-being, caused enjoyment and fulfilment, and at the same time led to a moment to stress and related changes [1] . Globally, around 10% of women during pregnancy and 13% of women after a child birth experience mental disorders, particularly depression.…”
Section: Introductionmentioning
confidence: 99%